Draft Annual Plan 1988-89. Vol. III (In 4 Volumes) Haryana State - Planning Commission (Planning Commission, 1987)
During 1985, worst affected areas of the State were District. Sirsa, Hissar and Bind as a result of heavy Local rainfall. Not only rural areas but even urban areas in those districts wore affected. Relief was provided through existing drainage system and by resorting to dewatering on massive scale. Also during 1986, worst affected district wore Sirsa and Some parts of Fatohabad Tehsil of District Hissar.
Planning Department, Government of Haryana